Pushing the frontiers of Islamic finance through socially responsible investment sukuk - Kassim, Salina; Abdullah, Adam (IIUM Press, 2017)
This study explores the potentials of SRI sukuk as a source of financing for projects that address community and social issues, thus giving positive impact to the society. Focusing on several cases of SRI sukuk in critical yet not so commercially-attractive for profit-motivated financial institutions to participate in such as education, environment and health sectors, this study highlights the mechanisms and challenges as well as potentials of SRI sukuk as a source of financing for these projects. Since the field of SRI sukuk is still in its infancy stage especially in Islamic finance, this study hopes to contribute towards enriching the literature as well as exploring the potentials for further applications in other areas in the Islamic finance industry.